Bioaggressors of the olive tree in a semi-arid region: identification, characterization, and biocontrol alternatives using essential oils of Rosmarinus officinalis and Cupressus sempervirens - Oubraham Farid; Reguieg Salima; Chaibi Rachid; Benhassine Mohamed Lamine (International Journal of Computational and Experimental Science and Engineering, 2026)
The olive tree represents a major arboricultural resource in Algeria; however, its cultivation is threatened by various bioaggressors. This study aims to inventory fungal infestations and olive pests in the Laghouat region and to evaluate the effectiveness of natural alternatives to chemical pesticides. The methodology is based on three main approaches:(i) identification of pathogenic fungi sampled from different parts of the olive tree and the surrounding soil;(ii) extraction by hydrodistillation of essential oils (EOs) from Rosmarinus officinalis and Cupressus sempervirens;(iii) evaluation of their in vitro antifungal activity through direct confrontation against phytopathogenic fungi, combined with an inventory of entomofauna using various trapping techniques.The results led to the identification of five fungal strains (Fusarium solani, Fusarium sp., Penicillium sp., Colletotrichum sp., and Alternaria sp.), with extraction yields of 0.51% for R. officinalis and 0.39% for C. sempervirens. Antifungal tests revealed that pure rosemary essential oil exerted total inhibition (100%) against F. solani and significant inhibition (80%) against Fusarium sp., whereas cypress essential oil showed inhibition rates of 66.67% and 71.43%, respectively. Even at reduced concentrations (25% and 50%), both essential oils maintained inhibitory activity exceeding 50%.The entomological survey identified 11 species, including 5 natural predators, with a predominance of Hymenoptera (29%). These results confirm the potential of essential oils as promising biopesticides for the sustainable management of olive tree bioaggressors.